1993
DOI: 10.4319/lo.1993.38.6.1276
|View full text |Cite
|
Sign up to set email alerts
|

Effects of algal density and current on ion transport through periphyton communities

Abstract: The effects of periphyton density and current on rates of nutrient transport from the water column through periphyton were measured with periphyton on glass-fiber filters. The flux of NO, and Si was inversely related to periphyton density, but Cl flux was affected only by the highest periphyton densities. The relatively greater decreases in NO, and Si flux than in Cl flux with increases in periphyton density indicated that nutrient uptake by periphyton affected nutrient transport through periphyton. The negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 0 publications
2
47
0
1
Order By: Relevance
“…However, it is not known whether algal taxa that responded to nutrient ratio did so through exploitative competition for nutrients, which is assumed by theory (Tilman 1982). Nutrient availability is lower at the base of periphyton mats than at the surface (Stevenson and Glover 1993). For exploitative competition for nutrients to occur, however, nutrient uptake rates must approach supply rates, which has yet to be documented for periphyton mats in flowing waters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not known whether algal taxa that responded to nutrient ratio did so through exploitative competition for nutrients, which is assumed by theory (Tilman 1982). Nutrient availability is lower at the base of periphyton mats than at the surface (Stevenson and Glover 1993). For exploitative competition for nutrients to occur, however, nutrient uptake rates must approach supply rates, which has yet to be documented for periphyton mats in flowing waters.…”
Section: Discussionmentioning
confidence: 99%
“…Periphyton mat thickness likely affected nutrient availability to algae, especially those in lower layers, because of limitation of the rate of nutrient diffusion from bulk water into the mat (Bothwell 1989;Burkholder et al 1990;Stevenson and Glover 1993). Pringle (1990) found that algal taxa in the upper layers of periphyton appeared to interfere with inorganic nutrient procurement by understory sessile taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Under conditions of high light and nutrient excess, growth rates of marine phytoplankton appear to be limited by carbon dioxide supply (Riebesell et al 1993). The notion that periphyton biomass accrual may be self-limited through biomass barriers to nutrient diffusion or through selfshading is not new Stevenson and Glover 1993), but self-limitation due to carbon depletion within the periphyton matrix has seldom been invoked as a constraint on periphyton development. Carbon limitation in alkaline waters may affect maximum biomass development more than accrual rate, and it may be demonstrable only after a threshold amount of periphyton biomass has accrued.…”
Section: Discussionmentioning
confidence: 99%
“…Low velocities are likely to exacerbate carbon depletion within periphyton, increasing d 13 C values already elevated in thicker periphyton. Unfortunately, water velocity and periphyton biomass often covary (Stevenson 1996), making it difficult to disentangle the effects of the two variables. Low periphyton biomass can result from high water velocities, and both low biomass and high velocity would be predicted to increase 13 C in periphyton.…”
Section: Discussionmentioning
confidence: 99%
“…3A to D) suggests the existence of this transport. In the case of riverine stromatolites, such as that of La Solana, water velocity can enhance the diffusion of dissolved nutrients and gases throughout the whole structure (Stevenson & Glover 1993). The boundary layer that limits diffusion decreases with fluid motion (Allan 1995), being inversely related to water velocity and therefore providing additional advantage in fast-flowing streams.…”
Section: Discussionmentioning
confidence: 99%